Jane Austen and the fiction of her time - Waldron, Mary (Cambridge University Press, 1999)
This book presents Jane Austen as a radical innovator. It explores the nature of her confrontation with the popular novelists of her time, and demonstrates how her challenge to them transformed fiction. In thus identifying her literary motivation, this book offers a fresh and unifying critique of the novels.